“How Danish do you need to be to be Danish?” How young second-generation immigrants of Middle Eastern descent perceive the possibilities of belonging in Denmark - Simonsen, Kristina Bakkær (Politica, 2017)
Research on integration of immigrants and their children typically focuses on functional and objective measures, while the identificational dimension of integration is seldom examined. On the basis of in-depth interviews, I analyze how young second-generation immigrants of Middle Eastern descent perceive the boundary to the Danish nation, including the effect of these perceptions on their feelings of national belonging. The analysis shows that there is widespread consensus among the interviewees about the markers that exclude them from the Danish nation. However, the degree of belonging varies across interviewees (from secure identification to dis-identification); a variation that can be explained by how they perceive their own position in relation to the boundary.